THE IMPORTANCE OF FIQH RULES IN ISLAMIC CIVIL LAW (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the significance, development and role of fiqh rules in the system of Islamic civil law, as well as their place in regulating legal relations. The works of outstanding legal scholars who substantiated and systematized fiqh rules are examined. The significance of customary law in fiqh rules is considered, and a comparative analysis of fiqh rules with modern procedural legislation is conducted.